Ефективність термолюмінесценції легованих тетраборатів літію : порівняльне дослідження монокристалічних та склоподібних зразків - Ignatovych, M. V.; Kelemen, A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
Comparative study on thermoluminescence efficiency of manganese and silver doped single crystal and glassy samples of tetraborate lithium was performed. The efficiency of charge traps based on parallel measurements of radioluminescence and thermoluminescence was evaluated. It has been shown, that this value for the single crystal samples is considerably different comparing to the glassy ones. The explanation was proposed, which is consisting with the experimental glow curves of thermoluminescence.